Analysis of Distance Learning Activities to Teach Collaboration Ability of Undergraduate Students of Mathematics Education Study Program - Palma, Dewi Isabella; Nadiasari, Eliana (Journal of Mathematics and Mathematics Education, 2022)
Distance learning is learning that is carried out separately between students and educators, the learning carried out is designed using communication tools or learning management media to support learning. In the 21st century, there are abilities that must be mastered by someone called 21st Century Competencies, one of which is the ability to collaborate. The purpose of this study is to describe distance learning activities to teach student collaboration skills and describe the influence of learning activities on distance learning in developing collaboration skills. This type of research is descriptive qualitative with a literature review method equipped with field data. The results showed that there are several things that need to be considered in designing distance learning activities to teach students' collaboration skills, namely 1) dividing students into groups, 2) using media that supports students to provide responses, ideas, comments and so on in the form of video conference forums and LMS, 3) instructions on feedback activities, and 4) the culture built in learning activities. Indicators of collaboration ability are also obtained, namely 1) cooperation and interdependence to achieve common goals such as cooperation in groups, discussion, active contribution, and flexibility, 2) being responsible for the basis of learning and behavior of each such as being responsible for work and working productively, and 3) the implementation of a cohesive work activity such as being able to adapt, communicate well,  and respect for others.  In addition, there are advantages and disadvantages of this design of distance learning activities.